Analisis Digitalisasi Pendidikan Terhadap Aksesibilitas, Kualitas dan Inklusivitas Pendidikan - Apriyenti, Apriyenti; Oktawira, Leni; Rahmi, Sri (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to analyze the digitalization of education on accessibility, quality and inclusivity of education. This research uses a literature study method, which involves collecting and analyzing relevant scientific sources, such as academic books, research articles, and other credible documents related to the research topic. The data collection technique is based on the selection of literature based on certain criteria, such as relevance to the topic, credibility of the source, and publication date to ensure the data is up to date. The data analysis technique uses a qualitative descriptive analysis approach, where the collected data is examined by identifying key themes, patterns, and concepts in the selected literature. The findings of this study are that digitalization of education has great potential to improve accessibility, quality, and inclusivity of education. There needs to be attention to infrastructure, teacher training, and programs that support students with special needs. Collaborative efforts from various parties can ensure that every individual can learn and develop in the digital era. Digitization of education has the potential to improve the accessibility and quality of education in Indonesia. Collaborative efforts between governments, schools, and technology companies are needed to develop infrastructure and learning materials that support the teaching and learning process effectively and inclusively